Answers

2015-04-20T20:12:46+05:30
Given : secx + tanx = p ................................... (i)
Now, we know that : sec²x - tan²x = 1
or, (secx + tanx)(secx - tanx) = 1

Putting (i) in the equation, we get :-
p(secx - tanx) = 1
or, secx - tanx = 1/p .........................................(ii)

Now adding (i) and (ii), we get :-
secx + tanx + secx - tanx = 1/p + p
or, 2secx = (1+p²)/p
or, secx = (1+p²)/2p   [Ans 1]

On subtracting (ii) from (i), we get :-
(secx + tanx) - (secx - tanx) = p - 1/p
or, 2tanx = (p² - 1)/p
or, tanx = (p² - 1)/2p    [Ans 2]

We know that sinx = sinx/cosx x cosx
or, sinx = tanx x 1/secx
or, sinx = tanx/secx
or, sinx = [(p² - 1)/2p]/[(p² + 1)/2p] ..(In the next step both the 2p get cancelled)
or, sinx = (p² - 1)/(p² + 1)    [Ans 3]

Hope that helps !!
9 4 9
In case u have any doubts, u an ask it here!!
Plz pick it as best if it was helpful !! :)